CO2‐fixing liquid droplets: Towards a dissection of the microalgal pyrenoid. (8th May 2019) - Wunder, Tobias; Oh, Zhen Guo; Mueller‐Cajar, Oliver
Abstract: CO2 enters the biosphere via the slow, oxygen‐sensitive carboxylase, Rubisco. To compensate, most microalgae saturate Rubisco with its substrate gas through a carbon dioxide concentrating mechanism. This strategy frequently involves compartmentalization of the enzyme in the pyrenoid, a non‐membrane enclosed compartment of the chloroplast stroma. Recently, tremendous advances have been achieved concerning the structure, physical properties, composition and in vitro reconstitution of the pyrenoid matrix from the green alga Chlamydomonas reinhardtii . The discovery of the intrinsically disordered multivalent Rubisco linker protein EPYC1 provided a biochemical framework to explain the subsequent finding that the pyrenoid resembles a liquid droplet in vivo. Reconstitution of the corresponding liquid‐liquid phase separation using pure Rubisco and EPYC1 allowed a detailed characterization of this process. Finally, a large high‐quality dataset of pyrenoidal protein‐protein interactions inclusive of spatial information provides ample substrate for rapid further functional dissection of the pyrenoid. Integrating and extending recent advances will inform synthetic biology efforts towards enhancing plant photosynthesis as well as contribute a versatile model towards experimentally dissecting the biochemistry of enzyme‐containing membraneless organelles. Abstract : Most microalgae sequester the CO2 ‐fixing enzyme Rubisco in a compartment known as the pyrenoid to enable a localized concentration of the gaseous substrate. It has recently emerged that the pyrenoid behaves as a phase‐separated organelle. Using Rubisco and an intrinsically disordered linker protein, a phase separation can be reconstituted in vitro enabling a bottom‐up biochemical characterization of the pyrenoid matrix.